Training of future general science teachers for productive methodical activity - Sergey Victorovich Shcherbatykh., Yevgeniya Nikolaevna Gerasimova, Natalya Viktorovna Morgacheva, (Opción, 2019)
The purpose of this article is to reveal the possibilities of higher education in the field of professional training of future general science teachers for productive methodical activity. The main method of research was a formative experiment. As a result, the research revealed the possibility to establish the correlation between the level of skills formation and capacities for productive methodical activity among students. In conclusion, young teachers staying in the profession is also attributed to the level of skills and abilities of productive methodical activity, as well as the experience of success and recognition.